Lean and Agile Supply Chain Practices in Indonesian Manufacturing: A Literature Review of Regional and Industrial Variations (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study examines the implementation of Lean and Agile supply chain practices in the Indonesian manufacturing sector, where firms face increasing pressure to balance operational efficiency and responsiveness in dynamic market environments. The study aims to review the application of Lean and Agile supply chain strategies across different industrial and regional contexts in Indonesia, as well as to identify the role of Agility in improving operational performance. A Literature Review approach based on the PRISMA framework was employed using literature collected from Google Scholar, Scopus, and ScienceDirect through Publish or Perish (PoP). The search covered studies published between 2015 and 2026 using keywords related to Lean supply chain, Agile supply chain, Leagility, and Indonesian manufacturing. Following the screening and eligibility process, 21 studies were included in the final review. The findings reveal substantial variation in the adoption of Lean and Agile supply chain practices across industries and regions. The automotive sector demonstrates the highest maturity in Lean–Agile integration through structured and efficiency-oriented operations, while the pharmaceutical industry is dominated by Agile-oriented strategies due to high demand uncertainty and responsiveness requirements. In contrast, agro-industrial SMEs exhibit limited capability to balance efficiency and flexibility, particularly in regions with infrastructural and resource constraints. The review further highlights Agility as a critical integrative capability that enables firms to align Lean efficiency with Agile responsiveness, thereby enhancing operational performance. Overall, the study concludes that isolated implementation of Lean or Agile practices is insufficient for sustainable supply chain competitiveness, and manufacturing firms should instead develop integrated supply chain capabilities that simultaneously support efficiency, flexibility, and responsiveness.
Keywords: Lean Supply Chain; Agile Supply Chain; Supply Chain Agility; Indonesian Manufacturing; Leagility